A Retrospective Study of Rare Listeria Meningoencephalitis in Immunocompetent Children in China - Mo, Tingting; Wu, Fang; Dou, Xiangjun; Wang, Dong; Xia, Han; Li, Xia (Frontiers in Neurology, 2022)
Objectives Listeria meningoencephalitis (LMM) is very rare in healthy children. We aimed to assess the clinical features, differential diagnosis, treatment options, and outcomes of LMM in immunocompetent children through a retrospective study. Methods The clinical symptoms, laboratory findings, imaging features, antibiotic use, and metagenomic next-generation sequencing (mNGS) results of the cerebrospinal fluid (CSF) were obtained from immunocompetent children who were diagnosed with LMM and admitted to the Xi'an Children's Hospital from May 2018 to July 2020. Results The data from 8 immunocompetent children were retrospectively analyzed in this study. The cohort included data from 5 males and 3 females who were aged from 1 year and 7 months to 16 years and 6 months. A total of 4 patients had chilled food before onset. The complications included hyponatremia (3/8), hydrocephalus (2/8), and hemophagocytic syndrome (1/8). In total, 8 patients were diagnosed with Listeria monocytogenes by positive CSF culture or mNGS results. The positive rate of CSF culture was 62.5% (5/8). A total of 5 patients conducted CSF mNGS, and the results of the mNGS were positive in 4 patients (80%, 4/5) and suspected in 1 patient. A total of 7 patients changed their therapeutic regimen to combined antibacterial therapies that included linezolid and meropenem (5/8), or ampicillin and meropenem (2/8). A total of 5 patients had favorable outcomes (Glasgow Outcome Scale, GOSE = 5) while two patients had unfavorable outcomes (GOSE = 1) and were complicated with hyponatremia and hydrocephalus. Conclusions Listeria meningoencephalitis (LMM) can occur in children with normal immune function and is commonly mistaken for other central nervous system infections. L. monocytogenes can be quickly and accurately detected by mNGS. Hyponatremia and hydrocephalus may indicate unfavorable outcomes.